The hepatoprotective effect of the combination use of Fructus Schisandrae with statin – A preclinical evaluation. (3rd February 2016) - Wat, Elaine; Ng, Chun Fai; Wong, Eric Chun Wai; Koon, Chi Man; Lau, Ching Po; Cheung, David Wing Shing; Fung, Kwok Pui; Lau, Clara Bik San; Leung, Ping Chung
Abstract: Ethnopharmacological relevance: Fructus Schisandrae is traditionally used as a liver-toning Chinese herb. Recent studies suggested Fructus Schisandrae could prevent high-fat diet-induced hepatic steatosis as well as improving anti-oxidative status within the liver, which is a proposed mechanism against statin-induced liver toxicity. Aim: The aim of the present study was to determine if the combination use of Atorvastatin (AS) and Fructus Schisandrae aqueous extract (FSE) could (a) exert potent therapeutic effects not only on high-fat diet-induced hyperlipidemia, but also on hepatomegaly (enlarge of liver size) and hepatic steatosis (fatty liver); and (b) reduce side effects caused by intake of statin alone including increased incidence of elevated liver enzymes and liver toxicity in Sprague Dawley rats. Materials and methods: We studied 5 groups of Sprague Dawley rats that were given the following treatment for 8 weeks: (i) Normal-chow diet; (ii) High-fat diet (contains 21% fat and 0.15% cholesterol); (iii) High-fat diet (contains 21% fat and 0.15% cholesterol)+0.3% Atorvastatin; (iv) High-fat diet (contains 21% fat and 0.15% cholesterol)+0.45% FSE; (v) High-fat diet (contains 21% fat and 0.15% cholesterol)+0.3% Atorvastatin+0.45% FSE. After 8 weeks of treatment, body weight, adipose tissue and liver mass were measured, and liver and plasma lipid levels were determined to evaluate to effect of FSE with or without AS treatment on diet-induced obesity, hyperlipidemia and hepatic steatosis. Liver enzyme activities, anti-oxidative status and membrane permeability transition were also assessed to determine if FSE could reduce the side effects induced by AS. Results: From the results, FSE treatment alone resulted in significant inhibitory effect on diet-induced increase in: (a) body weight; (b) fat pad mass (epididymal, perirenal and inguinal fat); (c) liver weight; (d) total liver lipid; (e) liver triglyceride and cholesterol levels; and (f) plasma lipid levels, suggesting FSE has a potential preventive beneficial effect on weight control and lipid metabolism in Sprague Dawley rats with diet-induced obesity. However, FSE supplementation exerted no further beneficial effect on diet-induced metabolic syndrome when it is combined with AS treatment, compared with rats given AS-treatment alone. At the dose of 0.45%, dietary FSE supplementation resulted in: (a) reduced liver enzymes (ALT and AST) levels; (b) reduced macrophage infiltration (CD68); (c) improved liver glutathione levels (anti-oxidative status); (d) reduced liver reactive oxidative species; (e) a trend to reduce calcium-induced membrane permeability transition within the liver. Most importantly, these improvements induced by FSE treatment were not only observed in the livers of rats given high-fat-diet, but also in high-fat-fed rats with atorvastatin-induced hepatotoxicity. Conclusions: Taken together, these data suggested FSE has a potential beneficial effect on weight control and lipid metabolism in Sprague Dawley rats with diet-induced obesity, and the combination use of FSE with AS could significantly prevent liver toxicity and anti-oxidative status induced by AS alone. Graphical abstract: